EDUKASI PEMBERIAN STRETCHING DAN NEUROMUSKULAR TAPING DALAM MENGURANGI NYERI HAID PRIMER (DISMENORE PRIMER) PADA REMAJA PUTRI - Ismaningsih .; Sara Herlina; Nurmaliza . (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Menstruation is a physiological thing that happens to every young woman. But in reality many women experience menstrual problems, including menstrual pain / dysmenorrhea. Menstrual pain / dysmenorrhea is a gynecological complaint due to an imbalance in the hormone progesterone in the blood, causing pain. About 20-90% of cases of menstrual pain occur during adolescence and are associated with physical activity restrictions and absences from school or work. Dysmenorrhea also causes learning activities in the learning process to be disrupted, concentration decreases and none even exists so that the material provided during ongoing learning cannot be captured by young women who are experiencing dysmenorrhea. Therefore dysmenorrhea in adolescents needs to get attention so as to provide appropriate non-pharmacological treatment. The aim of this program is to provide education and understanding to young women related to dysmenorrhea by giving appropriate interventions pharmacologically, namely by stretching intervention and neuromuscular taping. The location of this activity was carried out at SMA 2 Siak Hulu.. After training in adolescents about interventions that can be done for dysmenorrhea / menstrual pain measured using VAS. Evaluation results stated that from 21 people who were given intervention 19 people (90.5%) did not experience menstrual pain and 2 people (9.4%) experienced mild pain. It is expected that young women can find out information about the management of dysmenorrhea so as not to be absent and also unable to carry out daily activities at school or at home